2015
DOI: 10.1038/jcbfm.2015.89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endothelin Receptor Antagonists on Clinically Relevant Outcomes after Experimental Subarachnoid Hemorrhage: A Systematic Review and Meta-Analysis

Abstract: In clinical trials, endothelin receptor antagonists (ETRAs) reduced vasospasm but did not improve functional outcome after subarachnoid hemorrhage (SAH). We assessed the effects of treatment with ETRAs on clinically relevant outcomes in animal studies modelling SAH by performing a systematic review of the literature for controlled animal studies of ETRAs for the treatment of SAH. Primary outcomes were neurobehavioral outcomes and case fatality. Secondary outcomes were cerebral vasospasm and cerebral blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The study revealed that ETRAs caused 54% and 93% improvements (95% CI) in cerebral artery diameter and blood flow respectively. However, although the findings supported ETRA-mediated decrease in vasospasm, improvement in neurobehavior and fatality rate was not evident (Laban et al, 2015).…”
Section: Ace Inhibitors (Aceis) or Angiotensin II Receptor Blockers (mentioning
confidence: 69%
See 1 more Smart Citation
“…The study revealed that ETRAs caused 54% and 93% improvements (95% CI) in cerebral artery diameter and blood flow respectively. However, although the findings supported ETRA-mediated decrease in vasospasm, improvement in neurobehavior and fatality rate was not evident (Laban et al, 2015).…”
Section: Ace Inhibitors (Aceis) or Angiotensin II Receptor Blockers (mentioning
confidence: 69%
“…1263 untreated patients served as control. The study detected that statin pre-treatment could cause a significant reduction in CRP (95% CI; p = 0.02) and AF (95% CI; p = 0.003), without having marked impact on MI (95% CI; p = 0.62), suggesting the selective efficacy of statin pretreatment in cardiac patients with CABG (An, Shi, Liu, Ma, & Ma, 2017 An et al (2017) Statins, thrombolytics, antithrombotics, anticoagulants and neuroprotectants Liu et al (2018) Chinese herbal injections Cerebrovascular Gouya et al (2014) Aspirin + clopidogrel El Sayed et al (2018) Cerebrolysin, citicoline and piracetam Laban et al (2015) Endothelin receptor antagonist Roberts et al (2012) Barbiturates…”
Section: Ace Inhibitors (Aceis) or Angiotensin II Receptor Blockers (mentioning
confidence: 99%
“…The inclusion of death as an outcome measure in experimental SAH studies may be critical in determining the true efficacy of a potential therapeutic agent, because SAH is a disease with a high mortality, and therefore, excluding animals that have died from the study may skew the results so that findings are biased toward surviving animals. The authors thus concluded that there was no evidence from animal studies that treatment with an endothelin receptor antagonist improved clinically relevant outcomes after SAH, while the reduction in cerebral vasospasm observed in animal studies was consistent with that observed in clinical trials, an effect that was not associated with better functional outcome in patients [30]. The different outcomes between experimental and clinical studies may also occur due to misinterpretation of data and confused terminology and definitions [31].…”
mentioning
confidence: 94%
“…To make systemic reviews more useful, publication bias or an overestimation of the effect of a treatment has to be avoided by reporting negative and neutral results and promoting data sharing [1], and making systematic reviews of animal studies a routine is our scientific and societal responsibility, just as with clinical studies in humans not simply for transparency but also to avoid waste of financial resources and unnecessary duplication of animal studies [12]. In a SAH research, a systematic review of animal studies of endothelin receptor antagonists was reported after the clinical trials were failed [30]. The review revealed that various animal models including both sexes and primate models were used, but randomization of treatment groups and blinded assessment of outcome were performed only in the half of experiments.…”
mentioning
confidence: 99%
“…EBI is the product of pathological mechanism triggered by oxidative stress, inflammation, cell death and so on, the mechanism of which needs to be elucidated (Hasegawa, Suzuki, Sozen, Altay, & Zhang, 2011; Sehba et al., 2011). Increasing evidence presented that inflammatory response and oxidative stress were involved in the mechanism of CV following SAH (Laban et al., 2015; Zhao, Wen, Dong, & Lu, 2016). These two devastating injured mechanisms were assessed in this study.…”
Section: Introductionmentioning
confidence: 99%